Preliminary Study of Physical and Chemical Stability of Polyherbal Suspensions by UV-Vis Spectrophotometry - Nining, Nining; Nursal, Fith Khaira (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Allicin, the main bioactive compound in garlic, contributes to its pharmacological effects. Monitoring the physical and chemical stability of herbal preparations is essential for ensuring product quality. This study aimed to evaluate the stability of a polyherbal suspension containing garlic, lemon, red ginger, honey, and apple cider vinegar. The suspension was assessed for physical properties (pH, viscosity, specific gravity, and particle dispersion) and chemical stability, focusing on thiosulfinate (TS) content. Measurements were taken over a period of five weeks under three different storage temperatures. TS levels were analyzed spectrophotometrically. The suspension had a specific gravity of 1.114 ± 0.002 g/mL and a pH of 3.74 ± 0.03. Both storage time and temperature significantly influenced pH, viscosity, and TS content (p<0.05), though all remained within acceptable pharmaceutical limits. TS degradation followed second-order kinetics. The polyherbal suspension demonstrated good physical stability over a five-week period. However, TS levels declined over time at all storage temperatures, indicating a trend toward reduced chemical stability.